Dial 911 for Murder: The Impact of Emergency Response Time on Homicides - Thomas Stratmann; David Chandler Thomas (Center for Economic Studies and ifo Institute (CESifo), 2016)
Several theories have been offered to explain the recent declines in violent crime rates in the United States. We hypothesize that technological innovations, which improved information transmission and shortened the response time between an aggravated assault incident and treatment, reduced the cost of saving lives and caused much of the decline in homicide rates in recent decades. Using difference-in-differences and event studies, we show that improvements in emergency services (9-1-1) caused significant decreases in homicide rates. Various falsification tests support these findings.
Keywords: D00; I10; K00; 330; homicides; aggravated assault; response times; value of time; 9-1-1